Climate-Smart Agriculture in Sri Lanka - World Bank; International Center for Tropical Agriculture (2016)
The climate-smart agriculture (CSA) concept reflects the ambition to improve the integration of agriculture development and climate responsiveness. CSA aims to achieve food security and broader development goals under a changing climate and increasing food demand. CSA initiatives sustainably increase agriculture productivity, enhance resilience of agro-systems, and reduce/remove greenhouse gases (GHGs) from agriculture production, and require planning to address tradeoffs and synergies between these three pillars: productivity, adaptation, and mitigation [1]. While the concept is new, and still evolving, many of the practices that constitute CSA already exist worldwide and are used by farmers to different degrees to cope with various production risks [2]. Mainstreaming CSA requires a critical stocktaking of existing and promising agricultural production practices for the future, and of institutional and financial enablers for CSA adoption. This country profile provides a snapshot of a developing baseline created to initiate the discussion about entry points for investing in and scaling up CSA in Sri Lanka.